TACHYON ENERGY IN THE QUANTUM-GRAVITATIONAL MAPPING - Николай Григорьевич Толмачев; Виктор Иванович Рябков (Авіаційно-космічна техніка та технологія, 2018)
The article presents a mapping of tachyon energy in the form of quantum-energy interaction of baryon and tachyon quanta on the basis of the quantum-gravitational approach. A baryon quantum means a portion of the already known baryonic substance with the interaction transmission rates equal to or less than the speed of light, and under a tachyon quantum means a portion of a previously not observed substance – the "dark" mass with interaction rates greater than the speed of light. On the basis of such assumptions, and also with the use of the basic laws of classical mechanics and the first two principles of thermodynamics, quantum-energy models have been developed in the work that allowed all the physical parameters of micro- and nanoparticles, such as masses, densities and temperatures, interaction transmission rates etc. to be represented in a form of their energy equivalents: Екб, Епб, Ект, Епт, ΔЕб and ΔЕт. With the help of such models it has been established the following: – the tachyon quantum actually possesses all the signs of matter, that is, it has mass, density, and all other physical parameters; – regarding the energy properties, that is, the kinetic and potential energies, the tachyon quantum exceeds the baryonic quantum by about 70 ± 100 orders of magnitude, that is, it has colossal energy, which is usually called as tachyon energy. The proof of the proper use of quantum-energy models for estimating the parameters of tachyon energy carriers in this paper was done in the way of comparing the values of known physical constants (normal pressure, normal temperature, normal molar volume, Loschmidt number, Boltzmann constant, Stefan-Boltzmann constant and universal gas constant) with their numerical values, obtained experimentally by different researchers at different times.